Democracy’s Discontent and the Resurgence of Military Coups in Africa - Odigbo, Jude; Ezekwelu, Kingsley Chukwudubem; Okeke, Remi Chukwudi (Journal of Contemporary International Relations and Diplomacy, 2023)
Post-colonial Africa is fraught with myriads of endogenous and exogenous challenges. This paper argues that decades of deplorable democratic experience in Africa have rather reincarnated some sorts of discontents and rebellious confrontation in some states in Africa. This is exemplified in the recent military coups in Sudan, Ethiopia, Central African Republic, Mali, Burkina Faso and the failed coups in Guinea Bissau and Gambia. The study utilizes documentary methods of data collection and adopts frustration-aggression theory in explaining the contradictions that appeared to have stultified democracy in Africa which apparently have denied the people the corresponding gains embedded in democratic practice. It concludes that ending the resurgence of military coups in Africa demands urgent steps to enthrone good governance in Africa’s democratic states. The paper recommends the institutionalization of governance in lieu of the prevailing personalization of state institutions in Africa.